Experimental investigation of vortex breakdown in a coaxial swirling jet with a density difference - A., Adzlan; H., Gotoda (Elsevier Ltd, 2012)
In this work we experimentally investigate the behavior of stable vortex breakdown taking place in a coaxial swirling jet with a density difference, highlighting the effect of the outer jet on the height of the stagnation point. With increasing bulk flow velocity of the outer jet, the degree of flow divergence decreases, resulting in an increase in the height of the stagnation point. This is due to a significant increase in the mean axial velocity along the centerline of the jet, which is clearly shown by particle image velocimetry (PIV). We proposed an equation to physically explain the height of the stagnation point in a coaxial swirling jet with a density difference undergoing vortex breakdown, by considering an estimate of the momentum balance in the flow, based on a simplified Navier–Stokes equation for coaxial jets with coannular flow. Even though the effect of the density difference on the height of the stagnation point is overestimated by the proposed equation, the increase with respect to the Reynolds number of the outer jet observed experimentally is in reasonably good qualitative agreement with the trend predicted by the theoretical model.